2002
DOI: 10.1083/jcb.200112106
|View full text |Cite
|
Sign up to set email alerts
|

Identification of myogenic-endothelial progenitor cells in the interstitial spaces of skeletal muscle

Abstract: Putative myogenic and endothelial (myo-endothelial) cell progenitors were identified in the interstitial spaces of murine skeletal muscle by immunohistochemistry and immunoelectron microscopy using CD34 antigen. Enzymatically isolated cells were characterized by fluorescence-activated cell sorting on the basis of cell surface antigen expression, and were sorted as a CD34+ and CD45− fraction. Cells in this fraction were ∼94% positive for Sca-1, and mostly negative (<3% positive) for CD14, 31, 49, 144, c-kit, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
311
1
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 313 publications
(341 citation statements)
references
References 33 publications
27
311
1
2
Order By: Relevance
“…Next, we looked for possible cell-surface markers of NMJcapping cells. A stem cell population located in interstitial spaces of skeletal muscle, outside the basal lamina, has been identified previously and isolated by immunostaining for the hematopoietic stem cell marker CD34 (Torrente et al, 2001;Tamaki et al, 2002). We found that the surfaces of NMJ-capping cells showed uniform, faint immunostaining for CD34 (Fig.…”
Section: Nmj-capping Cells Show a Distinct Immunocytochemical Profilesupporting
confidence: 55%
“…Next, we looked for possible cell-surface markers of NMJcapping cells. A stem cell population located in interstitial spaces of skeletal muscle, outside the basal lamina, has been identified previously and isolated by immunostaining for the hematopoietic stem cell marker CD34 (Torrente et al, 2001;Tamaki et al, 2002). We found that the surfaces of NMJ-capping cells showed uniform, faint immunostaining for CD34 (Fig.…”
Section: Nmj-capping Cells Show a Distinct Immunocytochemical Profilesupporting
confidence: 55%
“…3C and 3D. Although CD34 is a well characterized marker of hematopoietic precursors, some nonhematopoietic cells also express this marker (17,18,31,32). Consistent with our findings, CK7/8 has previously not been found in hematopoietic cells (9).…”
Section: Suskind Cd34 + Ck7/8 + Cells In the Fetal Liver Page 11 Of 26supporting
confidence: 88%
“…Expression of Bcrp1 was noted in CD34 þ /CD45 À murine myogenic-endothelial progenitor cells, which are resident in the interstitial spaces of mammalian skeletal muscle (Tamaki et al, 2002). BCRP expression has also been demonstrated in multipotential progenitor cells in islets isolated from adult human pancreas cells (Lechner et al, 2002).…”
Section: Expression and Function Of Bcrp In Stem Cellsmentioning
confidence: 98%